PENERAPAN GOOD CORPORATE GOVERNANCE PADA PERUSAHAAN KELUARGA DI BIDANG PERBANKAN (Studi Kasus pada PT BPR Arto Moro) - Abellando Biyakto Putra; Fuad Mas’ud (Diponegoro Journal of Management, 2023)
ABSTRACT In family companies, human resource management and company management are often carried out based on family considerations. To overcome this, it is necessary to apply the principles of good corporate governance. This study was conducted to determine how the implementation of good corporate governance in family companies engaged in the financial sector, and how it affects the company's performance. The research method used is qualitative research with a case study approach. Data sources consist of primary data, namely interviews and secondary data. The method of collecting data is through interviews, observation and document review in the form of documents, notes produced by BPR Arto Moro. The data obtained were then analyzed descriptively qualitatively. The results showed that PT BPR Arto Moro had implemented the principles of Good Corporate Governance (GCG) well including Transparency (openness of information), Accountability (accountability), Responsibility (responsibility), Independence, and Fairness. Although there is a slight potential conflict of interest arises because the Shareholder is concurrently the President Commissioner. Good implementation of GCG principles plus the leadership factor of family companies has a positive effect on company performance. This is because the leadership of family companies tends to be faster and bolder in making decisions.